PENGARUH GREEN BRAND POSITIONING, ATTITUDE TOWARD PRODUK RAMAH LINGKUNGAN TERHADAP GREEN PURCHASE INTENTION PADA MOTOR LISTRIK BENGKULU - Leo Aprianto; Adi Sismanto (UM. Bengkulu, 2026)
This study aims to analyze the influence of Green Brand Positioning and Attitude Toward Eco-Friendly Products on Green Purchase Intention among consumers of electric motorcycles in Bengkulu. The case study was conducted at the Uwinfly Bengkulu Nandar Dealer with a total of 45 respondents. The analysis method used is multiple regression analysis to determine the extent to which the independent variables affect the dependent variable both simultaneously and partially. The results of the study indicate that Green Brand Positioning has a positive and significant influence on Green Purchase Intention, meaning that the stronger the environmentally-friendly brand positioning is embedded, the greater the consumers' intention to purchase the product. Additionally, Attitude Toward Eco-Friendly Products also has a positive and significant influence on Green Purchase Intention, showing that a positive consumer attitude towards eco-friendly products encourages an increase in purchase intention. Simultaneously, these two independent variables significantly influence Green Purchase Intention. These findings imply that companies need to strengthen their environmentally-based brand positioning strategies and build positive consumer perceptions regarding product sustainability. Keywords: Green Brand Positioning, Attitude Toward Eco-Friendly Products, Green Purchase Intention, Electric Motorcycles